Development and validation of a tool to assess appetite of children in low income settings - Nahar, Baitun; Hossain, Muttaquina; Ickes, Scott B.; Naila, Nurun Nahar; Mahfuz, Mustafa; Hossain, Daluwar; Denno, Donna M.; Walson, Judd; Ahmed, Tahmeed (Science Direct, 2022)
This article was published in the Appetite [© 2018 Published by Elsevier Ltd.] and the definite version is available at: https://doi.org/10.1016/j.appet.2018.12.032 The Journal's website is at: https://www.sciencedirect.com/science/article/abs/pii/S0195666318304689?via%3Dihub